Faktor-Faktor yang Mempengaruhi Literasi Digital Remaja dalam Game Online: Sebuah Systematic Literature Review - Syanandi, Muhammad Destara; Hidayanto, Achmad Nizar (The Indonesian Journal of Computer Science, 2025)
The growing prominence of online games as spaces for intensive digital interaction has encouraged adolescents to engage more actively in gaming activities, while simultaneously increasing their exposure to various online opportunities and risks. This condition requires adolescents to possess adequate digital literacy skills, enabling them to navigate information, interact safely, and understand the social implications of their behaviour in virtual environments. This study aims to identify individual, social, and platform-level factors that influence adolescents’ digital literacy within the context of online games, and to explain how the relationships among these factors are discussed in prior empirical research. Using a Systematic Literature Review method based on PRISMA 2020, this study analyses 26 articles selected through a process of identification, screening, quality appraisal, and data extraction. The results demonstrate that adolescents’ digital literacy is influenced by individual competencies, such as digital skills, self-efficacy, critical thinking, and psychological conditions; social factors, including parental mediation, peer support, and socioeconomic conditions; and platform factors, including game feature design, interaction mechanisms, and characteristics of metaverse environments. The relationships among these factors are mutually reinforcing, in which digital literacy develops when a responsive social environment and safe platform design support individual competencies. This study highlights the importance of an ecological approach to understanding and enhancing adolescents’ digital literacy in online games. It encourages further research to explore more specific cultural contexts and game mechanics.